Aluminum alloy drill pipe in geothermal drilling : technical and economical opportunities - Anderson, Erin Rebecca (2009)
RES Master´s Thesis Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri The purpose of this investigation is to determine the application opportunities of aluminum alloy drill pipe (ADP) in geothermal drilling environments. The Geothermal Energy industry is at the tipping point of the global energy mix. Geothermal offers the benefits of other clean, sustainable energies such as low emissions but also boasts a small environmental footprint, base-load power, and widespread distribution as related to EGS applications. Additionally, with the improved development into ultra high energy extraction regions, the geothermal drilling industry is under high demand and is being tested to drill deeper, faster, and at reduced costs in order to make geothermal competitive economically and to satisfy energy demands. The achievement of greater drilling depths requires the advancement of the drilling industry to address limitations in the weight capacity of the drill rigs and the temperature limitations of the drilling components. Aluminum alloy drill pipes (ADP), sometimes referred to as Lightweight Aluminum Drill pipes (LADP) have been used in the drilling industry in Russia for many years. Due to ADP’s lightweight and high strength to weight ratio there are several advantages over conventional steel pipe. These advantages include the use of larger diameter drill pipe with thicker walls which increase annular flow; reduced pressure loss inside the drill pipe, resulting in smaller pump requirements; reduced derrick loads and hook loads due to reduced weight per length compared to steel and increased buoyancy effects in drilling fluids, resulting in smaller rigs or greater depth penetrations with current rigs; and reduced stresses in a number of drilling design parameters. The application ranges of ADP utilization will be studied in regards to temperature limitations, critical buckling loads and strength of materials, geothermal fluid chemistry, drilling fluid pressure losses and hydraulics, load ...